Strukturisasi Entity Relationship Diagram dan Data Flow Diagram Berbasis Business Event-Driven - Adi, Suroto; Kristin, Desi Maya (Bina Nusantara University, 2014)
Entity relationship diagram (ERD) and data flow diagram (DFD) modeling are necessary parts in analysis and design of structured information systems in business. Definition of entities in the ERD, the process, and datastore in the DFD have well described in a lot of literatures. However, practically it is not easy to explain how to design ERD and DFD models so that the students well understand the modeling steps, especially in business applications. This study discussed step-by-step systematic approach to ERD and DFD modeling using